Endovascular Thrombectomy for Acute Ischemic Stroke due to Calcified Cerebral Emboli - Hannes Schacht; Peter Schramm; Björn Machner; Björn-Hergen Laabs; Philipp J. Koch; Ulf Jensen-Kondering; Alexander Neumann (Stroke Research and Treatment)
Conclusion: First-pass reperfusion is less common in EVT of CCE. Also, there is a more frequent and severe infarct growth in CCE patients after EVT, which helps to understand the poorer clinical results. Thrombectomy devices optimized for CCE are desirable to improve outcomes in this subgroup of stroke patients.